Підготовчий документ до листа-угоди між Філоном Кмітою Чорнобильським та братією монастиря святого Миколи Пустинського (1584) - Березенко, Б.; Лукін, Д. (Сiверянський лiтопис, 2019)
The publication of this preparation document of agreement between Filon Kmita Chernobylsky and the Brothers of the monastery of St. Nicholas Pustinsky in 1584 gives an opportunity to better understand who Senator Filon Kmit was, how he acted, where he was, what he was interested in at the time, who were his comrades and who was around him communication. The published document is an attempt to answer these questions. In our plans, the publication and other documents related to the work of Filon Kmita in 1584-1587 years.